A Report on Finite Element Analysis of Oil and Gas Pipeline Buried in Soil Using Abaqus - VINAY N (2011)
INTERNAL GUIDE: RAVIKANTH TALLURI, MVJCE
Keywords: Analysis of Oil and Gas Pipeline Buried in Soil Using Abaqus